DESIGN AND ANALYSIS OF INCENTIVE MECHANISM FOR DISTRIBUTED FILE SHARING NETWORKS - Ibrahim, Ruqayyah Rabiu; Obunadike, G. N.; Bashir, Jamilu Ahmad (FUDMA JOURNAL OF SCIENCES, 2024)
Sharing of files and resources has been one of the main reasons for development on networking and the internet, the internet itself has been created for achieving this objective in a secured way and without loss of data or information. To successfully exchange files (such as movies, video files, audio, software systems, eBooks, etc.) over the Internet, a number of file peer-to-peer sharing systems (such as Bit-Torrent, Gnutella, suggested, eMule, UTorrent etc.) have been developed to counter the limitations of the server-client model. These platforms are used worldwide to share and download files by millions of Internet users. Users of these systems share files amongst themselves cooperatively. However, some nodes may want to exploit the system for their selfish purposes such as the common concept of consuming from the network resources without sharing, which is known as free-ridding. This phenomenon degrades the quantity of service of the network in addition to destroying trust among peers. To motivate peers to share their file chunks and achieve optimal quality of service in the network, an incentive mechanism is introduced in this study. The study employs mathematical modeling to represent the system, and the results showed that by using incentives to encourage node’s active participation, the problem of free-riding has been drastically reduced which in turn, reduces file download time.